KARAKTERISTIK ARSITEKTUR RUMAH ADAT WAJO DI KOMPLEKS MINIATUR BUDAYA SULAWESI SELATAN BENTENG SOMBAOPU MAKASSAR - Andi Annisa Amalia Annisa Amalia (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2014)
Characteristics Wajo custom homes in South Sulawesi Cultural Complex Miniature Somba Opu Makassar is a characteristic which has a typical value for custom home Wajo considered quite representative as one typology miniature traditional houses in South Sulawesi. There are several aspects that were analyzed from architectural aspects, namely: cosmology, layout, mass, layout, shape, material, structure and construction and ornament/decoration. The method used in traditional house miniature architectural characteristics Wajo is using the survey method (direct observation), where the data were analyzed by means of descriptive qualitative method.